Hybrid Technique for Vibration Control using Synchronized Switch Damping on Inductor Modal Approach and Shape Memory Alloy Integration - Yakoubi, Hadja; Cherif, Aida; Meddad, Mounir (International Journal of Membrane Science and Technology, 2023)
Vibration control is a critical aspect of various engineering applications, including automotive and aerospace systems. This research paper presents a novel approach to enhance the performance of the Synchronized Switch Damping on Inductor (SSDI) technique by incorporating Shape Memory Alloys (SMAs). SSDI has proven effective in managing energy dissipation during electronic switching transitions, mitigating voltage spikes and reducing electromagnetic interference. However, the method consumes a substantial amount of energy. In this study, we propose a hybrid approach that combines the benefits of SSDI with the unique properties of SMAs to achieve improved vibration control. The integration of SMAs introduces a semi-passive element to the system, exploiting the inherent properties of these alloys to undergo reversible shape changes in response to external stimuli. By strategically placing SMAs within the vibration-prone components of the system, we aim to harness the mechanical forces generated during shape recovery to counteract and dampen vibrations. This innovative approach aims to capitalize on the efficient energy conversion capabilities of SMAs, thus minimizing the additional energy consumption associated with traditional semi-passive methods. The research involves theoretical modeling and simulation studies to assess the effectiveness of the proposed technique. Preliminary results demonstrate a significant reduction in vibration amplitudes and enhanced damping capabilities, validating the potential of the integrated SSDI-SMA system. The findings of this study not only contribute to advancements in vibration control methodologies but also provide insights into the broader applications of SMA-enhanced semi-passive techniques in improving the overall performance and efficiency of systems.